2015
DOI: 10.4103/0972-9941.147699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical, functional, and oncological outcomes of open and robot-assisted partial nephrectomy

Abstract: BACKGROUND:We aimed to compare the surgical, oncological, and functional outcomes of robot-assisted partial nephrectomy (RAPN) with open partial nephrectomy (OPN) in the management of small renal masses.MATERIALS AND METHODS:Between 2009 and 2013, a total of 46 RAPN patients and 20 OPN patients was included in this study. Patients’ demographics, mean operative time, estimated blood loss (EBL), warm ischemia time (WIT), length of hospital stay, pre- and post-operative renal functions, complications and oncologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…suggests reduced operative complications, EBL and length of hospital stay in RAPN . Recent studies reinforce these findings . Similarly, our study demonstrated with statistical significance a benefit of RAPN over OPN in these perioperative parameters.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…suggests reduced operative complications, EBL and length of hospital stay in RAPN . Recent studies reinforce these findings . Similarly, our study demonstrated with statistical significance a benefit of RAPN over OPN in these perioperative parameters.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest RAPN is at least equivalent to OPN and favours its potential for renal preservation in more complex tumours. Furthermore, there was no significant difference in operation time between groups ( P = 0.16) despite our RAPN series accommodating the surgeons’ learning curve (i.e. the first 50 cases), suggesting early plateau of the RAPN learning gradient as proposed in earlier reports …”
Section: Discussionsupporting
confidence: 65%
“…Open partial nephrectomy has long been considered the treatment of first choice for T1 small renal masses (SRMs) [ 18 ]. Recently, there has been a move towards less invasive procedures such as laparoscopic and robotic partial nephrectomy [ 19 , 20 ]. RPN seems to be the currently more widely used method, in experienced centres, due to the added benefits offered by the da Vinci robot (such as improved precision and decreased range of motion) leading to decreased warm ischaemic times [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to the study by several other authors viz. Boylu [21][22][23][24][25]27 This difference may be attributed due to complains of fever in the postoperative period in 8 (16%) patients and persistent drainage in another patient.…”
Section: Onss Versus Rnssmentioning
confidence: 99%